JALUR ALTERNATIF SEBAGAI PENYELESAIAN SENGKETA TANAH - Nita Andinia Tri Pramesti; Nazwa Rizqita Rahmadani (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
Since September 24 1960, disputes regarding land disputes have arisen due to inconsistent, overlapping and conflicting government policies. So Law no. 5 of 1960 concerning Basic Agrarian Principles Regulations (UUPA) which have been ratified with the issuance of sectoral regulations such as mining regulations, forestry regulations, regional government regulations (Autonomy), each of which has placed its land on an object. The purpose of this research is how to alternatively resolve land disputes in the context of disputes between disadvantaged parties over their rights to the land. The method used in this research, if seen from its type, is that this research is included in the type of normative legal research by means of document study, whereas seen from its nature, this research is descriptive in nature, namely to provide a clear and detailed picture of the main problem being studied. . The results of the discussion show that Agrarian Law is a collection of laws, each of which regulates control rights over natural resources consisting of land law, water law, mining law, fisheries law, control law over energy and elements in outer space. The conclusion obtained from this research is that applying alternative routes in resolving land disputes must be done to reach mutual agreement. So that the parties can obtain legal certainty regarding their rights and a sense of justice in the problems they experience and ways to defend the rights they should have.